PENGARUH PEMBERIAN KONSELING DENGAN MEDIA E-BOOKLET TERHADAP PENGETAHUAN IBU NIFAS TENTANG GIZI MASA LAKTASI - Mauluddina, Faulia; Veradilla; Alza (LPPM STIKes Mitra Adiguna, 2025)
The postpartum period (puerperium) is the period that begins after the placenta comes out and ends when the uterine organs return to their original state (before pregnancy). The postpartum period lasts approximately 6 weeks. As an effort to prevent nutritional needs from being met during the postpartum period, it is necessary to increase maternal knowledge by providing counseling using e-booklet media. The aim of the research is to determine the effect of providing counseling using e-booklet media on postpartum mothers' knowledge about nutrition during lactation at PMB Husniyati Palembang in 2023. The scope of this research is postpartum mothers at PMB Husniyati Palembang. The research design was comparative cross sectional and the research sample was 33 people using purposive sampling technique. The data analysis used was the Wilcoxon test. The results obtained from the Wilcoxon test statistical test obtained a p value = 0.000. In conclusion, there is an influence of providing e-booklet media on postpartum mothers' knowledge about nutrition during lactation. Suggestions to health workers, especially midwives, can provide counseling to post-partum mothers regarding nutrition during lactation using e-booklet media and more optimally or more effectively by using WhatsApp for post-partum mothers.